Identification of natural resistance mediated by recognition of Phytophthora infestans effector gene Avr3aEM in potato - Elnahal, A.; Li, J.; Wang, X.; Zhou, C.; Wang, J.; Lindqvist-Kreuze, H.; Meng, Y.; Shan, W. (Frontiers Media, 2020)
Late blight is considered the most renowned devastating potato disease worldwide. Resistance gene (R)-based resistance to late blight is the most effective method to inhibit infection by the causal agent Phytophthora infestans. However, the limited availability of resistant potato varieties and the rapid loss of R resistance, caused by P. infestans virulence variability, make disease control rely on fungicide application. We employed an Agrobacterium tumefaciens-mediated transient gene expression assay and effector biology approach to understand late blight resistance of Chinese varieties that showed years of promising field performance. We are particularly interested in PiAvr3aEM, the most common virulent allele of PiAvr3aKI that triggers a R3a-mediated hypersensitive response (HR) and late blight resistance. Through our significantly improved A. tumefaciens-mediated transient gene expression assay in potato using cultured seedlings, we characterized two dominant potato varieties, Qingshu9 and Longshu7, in China by transient expression of P. infestans effector genes. Transient expression of 10 known avirulence genes showed that PiAvr4 and PiAvr8 (PiAvrsmira2) could induce HR in Qingshu9, and PiAvrvnt1.1 in Longshu7, respectively. Our study also indicated that PiAvr3aEM is recognized by these two potato varieties, and is likely involved in their significant field performance of late blight resistance. The identification of natural resistance mediated by PiAvr3aEM recognition in Qingshu9 and Longshu7 will facilitate breeding for improved potato resistance against P. infestans.